An econometric analysis of cocoa prices: a structural approach - Shamsudin, Mad Nasir; Chew, Tek Ann; Rosdi, Mat Lani (Penerbit Universiti Kebangsaan Malaysia, 1992)
The world market model for cocoa was developed to examine the factors affecting cocoa prices. The models were used to analyse the interrelationship between the economic variables of supply, demand, price and stocks. The findings indicate that the important determinants of cocoa prices are the stock levels and consumption.